A Plasma‐Triggered O−S Bond and P−N Junction Near the Surface of a SnS2 Nanosheet Array to Enable Efficient Solar Water Oxidation. (26th September 2019) - Meng, Linxing; Zhou, Xiaolong; Wang, Siyu; Zhou, Yu; Tian, Wei; Kidkhunthod, Pinit; Tunmee, Sarayut; Tang, Yongbing; Long, Run; Xin, Yu; Li, Liang
Abstract: A photoelectrochemical (PEC) cell can split water into hydrogen and oxygen with the assistance of solar illumination. However, its application is still limited by excessive bulk carrier recombination and sluggish surface oxygen evolution reaction (OER) kinetics. Taking SnS2 as an example, a promising layered optoelectronic semiconductor, Ar plasma treatment strategy was used to introduce a SnS/SnS2 P−N heterojunction and O−S bond near the surface of a SnS2 nanosheet array, simultaneously increasing the separation efficiency of photogenerated electron–hole pairs in the bulk and lowering the OER overpotential at the surface. The onset potential of the plasma‐treated SnS2 nanosheet array shifts negatively to 0.16 V, and the photocurrent density at 1.23 V vs. RHE boosts to 2.15 mA cm −2, which is 7 times that of pristine SnS2 . This work demonstrates a facile plasma treatment strategy to modulate the energy band structure and surface chemical states for improved PEC performance. Abstract : Ein Argonplasma wurde genutzt, um P‐N‐Heterokontakte und O‐S‐Bindungen nahe der Oberfläche einer SnS2 ‐Nanoschichtanordnung einzuführen. Auf diese Weise wird die Trenneffizienz photogenerierter Elektron‐Loch‐Paare im Volumen erhöht und die OER‐Überspannung an der Oberfläche gesenkt. Die plasmabehandelte Probe zeigte einen 7‐mal höheren Photostrom als von ursprünglichem SnS2 .